The Impact of COVID-19 on the Timing of Rotator Cuff Repair and Method of Postoperative Follow-up - Kevin C. Wang; Liam R. Butler; Christopher A. White; Akshar V. Patel; Bradford O. Parsons; Paul J. Cagle (Revista Brasileira de Ortopedia, 2023)
Abstract Objective Rotator cuff repair (RCR) is one of the most common arthroscopic procedures. Our investigation aims to quantify the impact that the COVID-19 pandemic had on RCR, specifically on patients with acute, traumatic injuries. Methods Institutional records were queried to identify patients who underwent arthroscopic RCR between March 1st to October 31st of both 2019 and 2020. Patient demographic, preoperative, perioperative, and postoperative data were collected from electronic medical records. Inferential statistics were used to analyze data. Results Totals of 72 and of 60 patients were identified in 2019 and in 2020, respectively. Patients in 2019 experienced shorter lengths of time from MRI to surgery (62.7 ± 70.5 days versus 115.7 ± 151.0 days; p = 0.01). Magnetic resonance imaging (MRI) scans showed a smaller average degree of retraction in 2019 (2.1 ± 1.3 cm versus 2.6 ± 1.2 cm; p = 0.05) butnodifference in anterior toposterior tear size between years (1.6 ± 1.0 cm versus 1.8 ± 1.0 cm; p = 0.17). Less patients in 2019 had a tele-health postoperative consultation with their operating surgeon compared with 2020 (0.0% versus 10.0%; p = 0.009). No significant changes in complications (0.0% versus 0.0%; p > 0.999), readmission (0.0% versus 0.0%; p > 0.999), or revision rates (5.6% versus 0.0%; p = 0.13) were observed. Conclusion From 2019 to 2020, there were no significant differences in patient demographics or major comorbidities. Our data suggests that even though the time from MRI to surgery was delayed in 2020 and telemedicine appointments were necessary, RCR was still performed in a time in early complications. Level of Evidence III.